Evaluation and comparison of Trachyspermum ammi seed extract for its anti-inflammatory effect - Aslam, Adeel; Nokhala, Ahmed; Peerzada, Sohaib; Ahmed, Shoaib; Khan, Tanveer; Siddiqui, Mohammad Jamshed Ahmad (Walters Kluwer, 2020)
Aims and Objectives: The present study was aimed to evaluate the anti-inflammatory effect of different seed extracts of Trachyspermum ammi at different doses. Materials and Methods: Three different seed extracts were prepared through Soxhlet extraction method by using n-hexane, chloroform and methanol solvents. Acute toxicity test performed at dose of 400 mg/kg, 800 mg/kg, 1600 mg/kg and 3200 mg/kg. Two different strengths of seed extracts (minimum therapeutic dose of 500 mg/kg and maximum therapeutic dose of 1000 mg/kg) were given to Wistar rats to measure anti-inflammatory activity through Carrageenan induced paw edema method. Results: The standard drug diclofenac sodium was (percentage of inhibition of paw edema 29.68%) more effective as compared to test drug. When efficacy of all extracts compared with each other, n-hexane extract showed more anti-inflammatory effect (percentage inhibition of paw edema 22.21%) at maximum effective dose 1000 mg/kg. Conclusion: Seed extracts of T. ammi showed anti-inflammatory activity by potentiating the neurotransmission of GABA and also by repression glutamate receptor.